2020
DOI: 10.1177/2158244020972361
|View full text |Cite
|
Sign up to set email alerts
|

Examining Burnout and the Relationships Between Job Characteristics, Engagement, and Turnover Intention Among U.S. Educators

Abstract: As a modern epidemic, burnout is the leading reason educators leave the profession. Guided by the job demands–resources theory, this study empirically examines the underlying processes associated with burnout and the direct relationships between job characteristics (i.e., job demands and job resources), turnover intention, and work engagement among a U.S. sample of educators ( n = 855). Although both job demands and job resources were positively related to work engagement, job demands had a stronger influence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 81 publications
(112 reference statements)
3
11
0
2
Order By: Relevance
“…For instance, Franco et al (2021) indicated that when teachers find themselves pressured by school authorities to act in a certain way, they are more likely to feel more exhausted and adopt more cynical attitudes toward their students. Similar results are found in D'Amico et al (2020), Russell et al (2020). In other words, there is a possibility that social workers experiencing JBO do not manifest all three aforementioned symptoms.…”
Section: Meaningful Work and Job Burnout Dimensionssupporting
confidence: 90%
See 2 more Smart Citations
“…For instance, Franco et al (2021) indicated that when teachers find themselves pressured by school authorities to act in a certain way, they are more likely to feel more exhausted and adopt more cynical attitudes toward their students. Similar results are found in D'Amico et al (2020), Russell et al (2020). In other words, there is a possibility that social workers experiencing JBO do not manifest all three aforementioned symptoms.…”
Section: Meaningful Work and Job Burnout Dimensionssupporting
confidence: 90%
“…In this regard, we have seen from other literature such as Bakker and de Vries (2020), Russell et al. (2020), Khaksar et al.…”
Section: Theoretical Frameworkmentioning
confidence: 76%
See 1 more Smart Citation
“…The author observed significant exhaustion and depleted motivation among the volunteers. Burnout has become a modern pandemic and is the primary cause of the increasing turnover rate among educators (Russell et al, 2020). Previous studies classified its causes into three categories based on the Job Demands-Resources model: job demands, job resources, and personal characteristics.…”
Section: B Burnoutmentioning
confidence: 99%
“…As a global concern, teacher burnout has been linked to a range of adverse outcomes across every stage of teachers’ careers ( Aloe et al, 2014 ). For example, teachers with burnout often report co-morbid psychological symptoms ( Wang et al, 2021 ), decreased job satisfaction ( Skaalvik and Skaalvik, 2009 ), and turnover intention ( Russell et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%